On-board controller design for quadruped wall climbing robot (Roboc UTM1) [microfilm] - 239133 Tan, Choon New (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001